RESULTS OF A MORPHOLOGICAL STUDY OF THE THYROID GLAND IN PATIENTS WITH AUTOIMMUNE THYROIDITIS - Sadikhov, F.G. (World of Medicine and Biology, 2023)
The purpose of the study was to conduct a morphological analysis of autoimmune changes in the thyroid gland in patients with autoimmune thyroiditis who received various treatment methods. The work is based on 481 patients' treatment results, including surgical and diagnostic material. Using data from fine-needle aspiration puncture biopsy and cytological examination of punctate samples, the nature of cytological changes in the thyroid gland was assessed. The diffuse-nodular form of autoimmune thyroiditis is characterized in most patients by an autoimmune process with goiter changes manifested by nodular and multinodular encapsulated formations. Outside of goiter changes, atrophic and sclerotic changes in the parenchyma and stroma of the gland, lymphoplasmacytic infiltration and oxyphilic cell transformation of the follicular epithelium are detected. Smaller transitional forms of B cells are observed in the foci of oxiphilic cell transformation. In the diffuse-pseudonodular form of autoimmune thyroiditis, the described changes persist in most patients but with less frequency (54.7–68 %).
Keywords: autoimmune thyroiditis; cytological changes; fine-needle aspiration biopsy